A Review on Diabetes Mellitus its Types, Pathophysiology, Epidermiology and its Global Burden - Patil, Sachin Rangrao; Chavan, Ajinkya Balasaheb; Patel, Ansar Mansur; Chavan, Pranjal Dhondiba; Bhopale, Jyoti Vilas (Journal for Research in Applied Sciences and Biotechnology, 2023)
The spread of obesity and unhealthy lifestyles has contributed to a significant and increasing disease burden associated with diabetes in all countries worldwide. According to recent estimates, the worldwide prevalence of diabetes in 2013 was recorded at 382 million individuals, with projections indicating a significant increase to 592 million by the year 2035. The categorization of diabetes based on its aetiology has gained widespread acceptance in the scientific community. There are two primary classifications of diabetes, namely type 1 and type 2. Type 2 diabetes is the predominant kind, constituting a majority proportion (>85%) of the overall prevalence of diabetes. Both types of diabetes have the potential to result in a range of problems affecting several bodily systems. These complications can manifest as microvascular endpoints such as retinopathy, nephropathy, and neuropathy, as well as macrovascular endpoints including ischemic heart disease, stroke, and peripheral vascular disease. Diabetes is a significant public health concern because to its association with premature morbidity, death, diminished life expectancy, and substantial financial and societal burdens. Diabetes mellitus is a chronic metabolic illness characterised by heterogeneity and a complex pathophysiology. The condition is distinguished by increased amounts of glucose in the bloodstream, known as hyperglycemia, which arises from irregularities in either the production of insulin or the effectiveness of insulin, or both. Traditionally, diabetes has been classified into three distinct types: Type 1 DM, also known as insulin-dependent diabetes mellitus (IDDM), characterised by the body's inability to make insulin, necessitating the administration of insulin by injections or the use of an insulin pump. This condition is commonly referred to as "juvenile diabetes" in medical literature. Type 2 diabetes mellitus, also known as non-insulin dependent diabetes mellitus (NIDDM), arises due to the presence of insulin resistance. This condition occurs when cells are unable to effectively utilise insulin, either with or without a complete absence of insulin. This particular classification was once denoted as "adult-onset diabetes". The third primary category is gestational diabetes, which manifests when women who do not have a prior medical history of diabetes experience elevated levels of blood glucose throughout their pregnancy. It is plausible that it may occur prior to the onset of type 2 diabetes mellitus. This article explores the various forms, pathophysiology, epidemiology, and global burden associated with the topic under discussion.